2017
DOI: 10.1038/srep39939
|View full text |Cite
|
Sign up to set email alerts
|

Association of regular physical activity with total and cause-specific mortality among middle-aged and older Chinese: a prospective cohort study

Abstract: Association between physical activity and mortality has rarely been investigated among the Chinese population. Furthermore, the most appropriate amount of physical activity for longevity benefits remains unclear. We used data from the Dongfeng-Tongji cohort, including 24,606 middle-aged and older retired adults in 2008 and followed to 2013, to quantify linear and non-linear dose-response relationships between regular physical activity and mortality risks by Cox proportional hazards model. Compared with partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…From 31 368 studies (excluding 3769 duplicate studies) identified through systematic literature searches, we included 48 prospective cohort studies 18–62. One of these studies comprised six individual cohorts18 and another nine individual cohorts 45.…”
Section: Resultsmentioning
confidence: 99%
“…From 31 368 studies (excluding 3769 duplicate studies) identified through systematic literature searches, we included 48 prospective cohort studies 18–62. One of these studies comprised six individual cohorts18 and another nine individual cohorts 45.…”
Section: Resultsmentioning
confidence: 99%
“…Participation in moderate intensity physical activity (PA) for at least 150 minutes a week was recommended by the World Health Organization for improving health benefits [1]. To date, many previous studies reported various health benefits and favorable influences of PA, such as a reduction in the risks of chronic diseases and death [2][3][4][5][6][7][8][9][10][11][12][13][14][15]. However, most of these studies were based on leisure time PA (LTPA) and its association with the risk of mortality.…”
Section: Introductionmentioning
confidence: 99%
“…The impact of physical activity pattern on health outcomes is an ongoing debate and has recently received considerable research attention 16 . It has been hypothesized, that long-term monitoring and pattern correction with respect to physical activity session frequency and distribution over time may facilitate rehabilitation and lead to a reduced number of deaths, caused by cardiovascular diseases 7,8 . This reasoning can be supported by the reported association between regularly and irregularly performed physical activity and survival after major cardiovascular events, i.e., myocardial infarction 1 , and stroke 9 .…”
Section: Introductionmentioning
confidence: 99%
“…This reasoning can be supported by the reported association between regularly and irregularly performed physical activity and survival after major cardiovascular events, i.e., myocardial infarction 1 , and stroke 9 . The majority of studies for assessing the association of physical activity and health outcomes involve metrics that rely only on the amount of physical activity, of which the step counts, energy expenditure, and a time spent in physical activity of a particular intensity are the most commonly used 8,10,11 . Since the conventional amount-based metrics do not account for physical activity session distribution over time, the pattern is not fully evaluated.…”
Section: Introductionmentioning
confidence: 99%